Evaluation of the frequency of consumption of vegetables, fruits and products rich in antioxidants by amateur and professional athletes - Wiktoria Staśkiewicz; Elżbieta Grochowska-Niedworok; Marek Kardas; Renata Polaniak; Mateusz Grajek; Agnieszka Białek-Dratwa; Małgorzata Piątek (Jan Długosz University in Częstochowa, 2023)
Athletes belong to a group with special nutritional needs. Strenuous physical activity causes an imbalance of oxidation reduction. The purpose of the study was to assess the frequency of consuming antioxidant-rich food products among amateurs and professionals practicing selected sports. A total of 119 athletes were included in the study. The study group consisted of amateur bodybuilders and Cross- Fit athletes, as well as professional football and handball players. A validated original questionnaire assessing the frequency of consumption of selected high-antioxidant products was used. The highest frequency of consuming raw fruits among amateur athletes was 5-6 times a week (40.68%, n = 24). Sport professionals usually reported 1 serving a day (26.67%, n=16). The highest frequency of consumption of raw vegetables was 2-4 portions a week (37.29%, n=22) in amateurs group, and 5-6 portions weekly (33.33%, n = 20) in professionals group. In addition, we evaluated the intake of red wine. Most of the amateurs (47.46%, n = 28) and professionals (41.67%, n = 25) did not consume wine. All the respond- ents consumed food products containing antioxidants in quantities that were much lower than those recommended. The obtained findings indicate the need to develop dietary recommendations on anti-oxidant-rich food products for athletes, as well as appropriate nutritional education.